Scheduled block time setting and on-time performance of U.S. and Chinese airlines—A comparative analysis. (December 2019) - Wang, Yanjun; Zhou, Ying; Hansen, Mark; Chin, Christopher
Abstract: Scheduled block time (SBT) is the duration between scheduled departure time and scheduled arrival time of a given flight. SBTs have a significant impact on airline operations and performance, and airlines consider various factors in setting them. Recent studies have proposed several models for understanding U.S. airlines' SBT-setting behavior and have examined the contribution of SBT-setting to airline on-time performance (OTP). How airlines in different countries and regions set their SBTs and to what degree differences in SBT-setting behavior explain observed differences in OTP is still unknown. Here we develop econometric models of SBTs based on historical distributions of actual block time to reveal the differences in SBT-setting behavior between major airlines in China and the U.S. We find that Chinese airlines focus on the left tail of the distributions while the U.S. airlines consider the left tail, middle, and inner right tail. They also have different ways of accounting for taxi-out time in setting SBTs, with the U.S. focusing on historical time distributions while in China taxi-out time is based on airport category. We then perform counterfactual analysis by using one nation's model to predict the other nation's SBTs and the resulting difference in OTP. Results indicate that the OTP of Chinese airlines would match those of the U.S. if they followed U.S. practices in setting SBTs, while U.S. airlines would have slightly worse OTP than Chinese carriers if they set SBTs according to Chinese methods. Our findings highlight the difference in SBT-setting behavior of major airlines in China and U.S. and its contribution to OTP. The model and methods presented here may also be applied to study and compare SBT setting and its impact on OTP in other parts of the world.